Manajemen Kanal Wireless Lokal Area Network Pada Dinas Kesehatan Kabupaten Sumba Timur - Katanga Mutu, Adipapa; Hariadi, Fajar; Asnath SitaniaPessy, Desy (Universitas Islam Balitar, 2024)
The health office is one of the offices in East Sumba district in charge of public health in the region. Health offices assisted by puskesmas in each sub-district aim to create equitable public health services. Currently, in general, health office employees use wifi networks to access the internet and there is no wifi channel management, so when accessing the internet there are often collisions / overlapping. The Health Office must be able to access national applications such as the Local Government Information System (SIPD) so that employees can input Work Plan and Budget (RKA) documents, Budget Implementation Documents (DPA) and many other applications. The purpose of this study is how to manage the wifi channel on the connected network so that there is no overlapping or collision when sending data. This study will be compared when overlapping occurs and after doing wifi channel management at the East Sumba Health Office. From the results of QOS (Quality Of Services) review, a comparison of packages before and after channel management is obtained. For comparison of changes in throughput, Packet loss, delay and jitter decreased in all areas, namely husada1, P2P and finance (kawa'dak). After calculation, the average throughput is -47.21%, Packet loss -90.21%, delay -58.14% and jitter -45.64% which means network quality based on throughput decreases while based on Packet loss, delay, and jitter increases due to Packet loss significantly reduced, packet delivery time and variation.